1964
DOI: 10.1037/h0040213
|View full text |Cite
|
Sign up to set email alerts
|

Combined MMPI and demographic data in predicting length of neuropsychiatric hospital stay.

Abstract: Data available on 316 psychiatric patients, soon after admission to a hospital, were used in a multiple regression formula and in less formal statistical techniques to predict length of stay. Demographic and MMPI predictors made possible early identification of long stay patients at greater than base rate frequency. The asymptote of prediction was reached when 6 of 24 variables had been included, suggesting that further search in the area would be redundant. Prediction with the 5 prediction schema was stable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

1966
1966
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…Consequently, it makes possible an earlier start on appropriate treatment and release for short-stay patients and the prompt beginning of appropriate treatment for long-stay patients. This would result in the more effective use of hospital facilities and staff (Anker, 1961;Dunham & Meltzer, 1946;Johnston & McNeil, 1964;McNeil, Johnston, & Aspromonte, 1970). The importance of a predictive index of length of hospital stay is also indicated in its use as an evaluative measure of patient program interaction, in addition to individual patient characteristics (Becker, 1975).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it makes possible an earlier start on appropriate treatment and release for short-stay patients and the prompt beginning of appropriate treatment for long-stay patients. This would result in the more effective use of hospital facilities and staff (Anker, 1961;Dunham & Meltzer, 1946;Johnston & McNeil, 1964;McNeil, Johnston, & Aspromonte, 1970). The importance of a predictive index of length of hospital stay is also indicated in its use as an evaluative measure of patient program interaction, in addition to individual patient characteristics (Becker, 1975).…”
mentioning
confidence: 99%
“…For example, simple demographic data (Chapman, Day, & Burstein, 1961;Chasson, 1963;Dunham & Meltzer, 1946;Lindemann et al, 1959;Schnore, 1963), the Minnesota Multiphasic Personality Inventory (MMPI) and other paper-and-pencil tests (Anker, 1961; Requests for reprints should be sent to J. J. Cyr, Psychology Department, Whitby Psychiatric Hospital, Whitby, Ontario, Canada LIN 5S9. Fulkerson & Barry, 1961), as well as a combination of these predictors (Johnston & McNeil, 1964;Munley et al, 1977) exemplify the kinds of variables used in this research area. Other predictor variables include influence of type of treatment (Becker, 1975) and demographic and social competence variables combined (Miller & Wilier, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the coding of the studies in table 4 was reliable, eight of the 11 studies (all but Johnston and McNeal [1964], Grant andBray [1970], andMcNees [1974]) were independently coded by two research assistants. The coding was blind in that the assistants were unaware of the hypotheses.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Studies of factors associated with length of hospitalization have been reported by Lindemann, Fairweather, Stone, Smith, and London (1959),' using demographic characteristics and clinical judgments, by Anker (1961) ,2 using MMPI responses, by Johnston and McNeal (1964) ,3 using MMPI scale scores and demographic characteristics, by Johnston and McNeal (1967),4 using clinical predictions, by Fulton and Lorei (1967) ,5 using life history variables, and by Daniel, Brandt, and Costiloe (1968) ,6 using demographic characteristics. With the exception of the latter study which was based on data from state mental hospitals in Oklahoma, all other studies were based on data collected from psychiatric patients in VA hospitals.…”
mentioning
confidence: 99%